2010
DOI: 10.1186/cc8888
|View full text |Cite
|
Sign up to set email alerts
|

Relative hyperlactatemia and hospital mortality in critically ill patients: a retrospective multi-centre study

Abstract: IntroductionHigher lactate concentrations within the normal reference range (relative hyperlactatemia) are not considered clinically significant. We tested the hypothesis that relative hyperlactatemia is independently associated with an increased risk of hospital death.MethodsThis observational study examined a prospectively obtained intensive care database of 7,155 consecutive critically ill patients admitted to the Intensive Care Units (ICUs) of four Australian university hospitals. We assessed the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
234
2
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(276 citation statements)
references
References 33 publications
17
234
2
12
Order By: Relevance
“…Similarly, lactatemia on admission to the ICU is a well-known prognostic and severity marker. 33,34 In the early postoperative period after LT, these factors could also be considered surrogate markers of inflammation or prothrombotic disorders induced by the surgery and liver graft function. The duration of postoperative mechanical ventilation after LT could also be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lactatemia on admission to the ICU is a well-known prognostic and severity marker. 33,34 In the early postoperative period after LT, these factors could also be considered surrogate markers of inflammation or prothrombotic disorders induced by the surgery and liver graft function. The duration of postoperative mechanical ventilation after LT could also be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that a lactate level of greater than 4 mmol/L, instead of 2 mmol/L, should be used to define hyperlactatemia to predict death [29]. Nichol et al [30], reported that high blood lactate concentrations within the current reference range were also associated with increased hospital mortality. In our study group, admission hyperlactatemia was not found to have a cutoff value to predict mortality by ROC analysis (Area under curve:0.57) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This will enable glycolysis, and the accompanying ATP production to proceed. (5) In other cases, lactic acidosis occurs because of an impairment in tissue oxygen utilization, as in septic shock and post resuscitation from cardiac arrest; a normal Smvo2 with an elevated lactate indicates such an impairment. Elevated lactate is a marker of impaired oxygen delivery and/or utilization and correlates with short-term prognosis of critically ill patients in the ED.Smvo2 can also be used as a measure of the balance between tissue oxygen supply and demand.…”
Section: Definitionmentioning
confidence: 99%